Alfabetização na EJA e a dispersão das práticas : escritas de abertura ao outro e leituras de mundo - Rodrigues, Henrique José Alves (2017)
This study addressed the theme related to Youth and Adult Literacy in a Youth and Adult Education (EJA) school at Vitória/ES. It aims to problematize the elaboration and distinctions between the youth and adult literacy policies and the literacy practices of students and teachers. The question that guided the investigative process was how the literacy policies and their conceptions were translated in the literacy practices that were observed/conducted. Based on the expanded notion of literacy in popular education, and on the concept of language as a pragmatic of deconstruction thinking, the notion of traslation, in this paper, brings the impossibility of fidelity to the original meaning, putting under suspicion the possibility of the policies that guide the practices to reach its original aims when put into practice, thus, we argue that the dispersive field of the practices always exceeds, runs away from the original sense or meaning of literacy policies established by international agencies, federal government and even the ones established by the school itself, which has popular education as a reference. This research was conducted in five literacy classrooms, guided by an intervention research design, which led us to adopt an ethics platform as a reading key to understand the production of data that were elaborated by the means of field journals, interviews with teachers and students, written productions records and school events. After analyzing the data, the following categories, concepts and notions emerged in the empirical plan: dialogue; language and literacy; popular culture and memory; writing culture; pratices of freedom and emancipation; democracy; law and justice. The research process has led us to conclude that the dispersion plan, that is, the heterogeneity of the forces, cross not only the literacy practices, but also the literacy policies, with their paradoxes, ambiguities, closures and creation breaches. People involved in literacy processes create innovative strategies, in order to move in a literate society and to give meaning to their own literacy process. . Despite the conceptual profusion in the EJA field, such strategies, although important, do not account for what happens in the process of literacy, which requires much more radical opening to the other person and attentively listening to their appeals, than coherent well defined theoretical references.